Persuading the Galatians A Text-Centred Rhetorical Analysis of a Pauline Letter - Tolmie, D. Francois (Mohr Siebeck, 2005)
Die Galater überzeugen. Eine textbasierte rhetorische Analyse eines Galaterbriefes.
PublicationDate: 20191210
Keywords: Neues Testament -- Pauline Letter -- Letter to the Galatians -- Sprachverständnis -- Array